In Memoriam: Prof D. R. Snaddon (The South African Journal of Industrial Engineering, 2025)
Prof Douglas Roy Snaddon (12 May 1944 - 18 August 2025) Prof Snaddon was Head of Industrial Engineering at the University of the Witwatersrand (Wits) for many years and held the prestigious Barloworld Chair of Industrial Engineering at Wits, building and steering the discipline with great vision, laying strong foundations and shaping a unique blend of Industrial Engineering suited to South African industrial needs. Prof Snaddon taught and inspired many students to love Industrial Engineering, which he promoted actively in South Africa and outside the country. In 2011, he left Wits to take up the position of Professor and Director of Mechanical Engineering at the Polytechnic of Namibia, where he started Industrial Engineering courses and qualifications in Namibia and encouraged the introduction of Industrial Engineering in Botswana. Prof Snaddon authored numerous papers and articles, as well as two books related to Industrial Engineering. He was an Honorary Fellow of the Southern African Institute for Industrial Engineering (SAIIE) and served on the SAIIE Council for many years, as well as President in 1994. During his retirement, Prof Snaddon kept regular contact with the Industrial Engineering Department of Wits University, giving the occasional lecture, providing valuable advice to the faculty, and regularly speaking at student evenings and prize-giving ceremonies. Prof Snaddon will be remembered for his incredible energy, drive, enthusiasm, wit, humour, forthrightness, non-compromise with excellence and kindness, generosity, and many other qualities. He will be dearly missed by all who knew him, particularly his children: Susan, Collin and Bruce and his grandchildren.